Differential bioaccumulation of mercury by zooplankton taxa in a mercury-contaminated reservoir Guizhou China. (August 2018) - Long, Sheng-Xing; Hamilton, Paul B.; Yang, Yang; Wang, Sai; Huang, Wen-da; Chen, Chuan; Tao, Ran
Abstract: Mercury (Hg) contamination in aquatic systems remains a global concern with the biomagnification of methylmercury (MeHg) through primary consumers (zooplankton) to fish and humans. In this study, total mercury (THg) and MeHg concentrations were analyzed in zooplankton collected from Baihua reservoir (Guizhou Province, China). Our results demonstrated that THg and MeHg concentrations were strongly correlated to zooplankton community and biomass composition. The THg concentration was significantly higher in micro-zooplankton compared to meso-zooplankton and macro-zooplankton, and MeHg concentration increased significantly as body size increased. Hg increases in zooplankton were influenced by the numbers of calanoid copepods and Daphnia present relative to phytoplankton and zooplankton biomass. Many zooplankton taxa in the three size-fractions were affected by THg exposure. The biomasses of Bosmina longirostris, Thermocyclops brevifurcatus, Asplanchna priodonta and Cyclops vicinus vicinus were positively correlated with Hg accumulation, while Daphnia hyalina, and Phyllodiaptomus tunguidus had a negative association. THg and MeHg bioaccumulation factors were correlated with phosphorus and total nitrogen concentration, zooplankton biomass, and chlorophyll -a concentration. Phosphorus loading was associated with increased THg and MeHg accumulation in the zooplankton highlighting biomagification with eutrophication. Chlorophyll- a levels were not correlated to THg and MeHg accumulation in zooplankton when phytoplankton densities were >10 7  cells L −1 and chlorophyll- a concentrations <9 μg L − 1 . This finding contradicts the idea of MeHg biodilution with increased algae biomass. However, changes in the phytoplankton species and biomass altered the availability of food for zooplankton, particularly micro-zooplankton and macro-zooplankton. Ultimately, the bioaccumulation of MeHg and THg across lower trophic levels was based more on the availability of preferred food resources than on total biological productivity. Graphical abstract: Image 1 Highlights: Hg bioaccumulation factors correlated with nutrients, plankton biomass, and chl -a. MeHg & THg concentration effected zooplankton body size. Species affected: B. longirostris T. brevifurcatus A. priodonta C. vicinus vicinus. Species not affected: D. hyalina, and P. tunguidus. MeHg & THg accumulation is more based on available food than bio-productivity.